The Specific Characteristics of Women in Religious Customs, Seasons and Customs in the Southern Regions of Uzbekistan (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article reflects the attention to women and girls in independent Uzbekistan and their religious views related to their activities, activities of religious authorities, religious holidays and customs, traditions and rituals performed with them.